1994
DOI: 10.1200/jco.1994.12.9.1859
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusion-modulated tumor recurrence: first results of a randomized study of autologous versus allogeneic blood transfusion in colorectal cancer surgery.

Abstract: As indicated by these first results, the blood transfusion modality has a significant effect on tumor recurrence after surgical treatment of colorectal cancer. A change in the practice of blood transfusion might thus potentially surpass the impact of any recent adjuvant treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
180
0
11

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(194 citation statements)
references
References 26 publications
3
180
0
11
Order By: Relevance
“…9 In addition, bleeding and blood transfusion are risk factors for postoperative morbidity and in some reports, long-term cancer recurrence. 6,[10][11][12][13][14][15][16][17][18][19][20][21][22] Furthermore, blood products are sometimes scarce and associated with appreciable expense. Thus, there is compelling rationale to reduce blood loss and blood transfusion as much as possible in patients undergoing liver resection.…”
Section: Introductionmentioning
confidence: 99%
“…9 In addition, bleeding and blood transfusion are risk factors for postoperative morbidity and in some reports, long-term cancer recurrence. 6,[10][11][12][13][14][15][16][17][18][19][20][21][22] Furthermore, blood products are sometimes scarce and associated with appreciable expense. Thus, there is compelling rationale to reduce blood loss and blood transfusion as much as possible in patients undergoing liver resection.…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44] Nevertheless, autologous or leukocyte-depleted transfusions did not improve outcomes for colorectal cancer patients, 45,46 suggesting that other non-immune-mediated factors may be responsible for poor outcomes. 47,48 Based on the information available in the present study, it is not possible to determine whether some unmeasured confounders may have contributed to our findings. Nevertheless, the results of two recent studies showed that perioperative blood transfusions were associated with worse oncological outcomes in patients with bladder cancer, albeit only in univariable analyses.…”
Section: Perioperative Transfusion and Oncological Outcomesmentioning
confidence: 85%
“…The role of hemolysis of RBCs in transfused blood in the predisposition to infections, multiple organ failure, and recurrence of cancer has been established but is not understood [13,14,66]. Lysed RBCs not only release Hb but also Cu,Zn SOD, catalase, phosphatidyserine, and phosphatidylethanolamine from the inner leaflet of the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Hemoglobin (Hb) is released from erythrocytes during hemolytic disorders, burns, and storage of blood for transfusion [7][8][9][10]. In humans, elevated levels of Mb or Hb have been reported to be associated with acute renal failure [11,12], infections, and recurrent cancers in postoperative patients receiving autologous and/or allogeneic transfused blood [13,14]. A recent report of higher mortality in trauma patients transfused with acellular, cross-linked oxyhemoglobin (oxyHb) solutions instead of stored red blood cells (RBCs) emphasizes the importance of elucidating the mechanism of heme protein toxicity [15].…”
Section: Introductionmentioning
confidence: 99%